2021
DOI: 10.3390/molecules26196065
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Hop Estrogen-Active Material for Production of Food Supplements

Abstract: In recent years, the interest in the health-promoting effects of hop prenylflavonoids, especially its estrogenic effects, has grown. Unfortunately, one of the most potent phytoestrogens identified so far, 8-prenylnaringenin, is only a minor component of hops, so its isolation from hop materials for the production of estrogenically active food supplements has proved to be problematic. The aim of this study was to optimize the conditions (e.g., temperature, the length of the process and the amount of the catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Additionally, the effects of hops in reducing adipocyte differentiation, increasing nitric oxide production, and regulating oestrogen are mentioned in the literature. This latter property has led to the emergence of hop-based products as potential supplements to support menopausal women [14][15][16][17]. The levels of these compounds are quite variable due to differences in the types of hop, the region where they grow, harvest times, and other changes caused by processing and brewing [2].…”
Section: Rising Interest In Nablabmentioning
confidence: 99%
“…Additionally, the effects of hops in reducing adipocyte differentiation, increasing nitric oxide production, and regulating oestrogen are mentioned in the literature. This latter property has led to the emergence of hop-based products as potential supplements to support menopausal women [14][15][16][17]. The levels of these compounds are quite variable due to differences in the types of hop, the region where they grow, harvest times, and other changes caused by processing and brewing [2].…”
Section: Rising Interest In Nablabmentioning
confidence: 99%
“…However, the industrial application of these prenylated flavanones has been limited due to their very low concentrations in hops and beer [42]. Against this backdrop, several attempts have recently been made to achieve a maximum yield of 8-PN in hop materials [13] or to develop an efficient synthetic method of 6-prenylnaringenin and 8-PN from xanthohumol [42]. In fact, through the magnesium oxide-catalyzed thermal isomerization of hop materials, the yield of 8-PN increased up to 70% relative to the starting material [13].…”
Section: Discussionmentioning
confidence: 99%
“…Against this backdrop, several attempts have recently been made to achieve a maximum yield of 8-PN in hop materials [13] or to develop an efficient synthetic method of 6-prenylnaringenin and 8-PN from xanthohumol [42]. In fact, through the magnesium oxide-catalyzed thermal isomerization of hop materials, the yield of 8-PN increased up to 70% relative to the starting material [13]. In addition, Schaefer et al [43] suggested the use of a radioimmunoassay for the quantitative determination of 8-PN in biological matrices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hops gives the characteristic aroma and bitter taste, based on functional ingredients, such as humulones, lupulones, 8-prenylnaringenin, 6-prenylanaringenin, xanthohumol, 6,8diprenylnaringenin and 8-geranylnaringenin, its healthy activities including antibiotic, anti-bacterial, anti-molds, anti-virus, anti-fungal, neuropreventive, estrogenic, and antinflamatory properties, especially prevent lots of chronic diseases, such as cancer, arthritis, insulin sensitivity, type II diabetes, metabolic syndrome, and menopause [9,71,72]. The estrogenic effects of hop prenylflavonoids is one of the most potent phytoestrogens identified so far, the yield of 8prenylnaringenin was 29 mg/100 g of product, which may be alleviated the symptoms of menopausal disorders [73] and over anticancer to estrogenic activity [74]. Xanthohumol in hop possess the synergistic effect against aging, diabetes, inflammation, microbial infection, anti-proliferative, and cancer [75,76].…”
Section: Hops For Human Healthmentioning
confidence: 99%